Beyond pigments and perfumes: engineering in the carotenoid and apocarotenoid spectrum, novel enzymes, and synthetic biology strategies - Ravi Gopal, Baradwaj; Wang, Zhen Q. (Frontiers in Bioengineering and Biotechnology, 2026)
Carotenoids and apocarotenoids constitute a structurally and functionally sundry class of isoprenoids whose significance extends from photosynthetic light capture and photoprotection to phytohormone signaling, flavor and aroma formation, and emerging biomedical applications. While recent appraisals have emphasized quantitative advances in microbial production, this mini-review adopts a pathway module-centric perspective. We examine each biosynthetic stage from precursor supply, condensation to geranylgeranyl diphosphate (GGPP), phytoene synthesis, desaturation/isomerization, cyclization, hydroxylation, ketolation, epoxidation, and oxidative cleavage, highlighting novel enzymatic variants, mutagenesis studies, fusion strategies, and compartmentalization approaches that impart metabolic control. Special emphasis is placed on recently discovered and engineered enzymes, as well as synthetic biology tools. This review integrates diverse enzyme sources, host ranges across plants, fungi, algae, yeasts, and bacteria, as well as pathway modularity, to provide an updated review of recent literature. We conclude by outlining future directions that highlight gaps and potential areas for future work. This focused synthesis aims to equip researchers with a hierarchical understanding of the pathways and strategies to advance carotenoid and apocarotenoid biosynthesis.